Strategi Pendampingan Passive Income Lansia dalam Menghadapi dan Menjalani Masa Tua di Yayasan Pendampingan Lansia Bojonegoro - Moch Suberi; Ruslina Yulaika; Ika Puspita Sari (Jurnal Pendidikan Edutama, 2023)
Abstract: The Elderly Assistance Foundation has a Vision: Delivering healthy, dignified elderly to Husnul Khotimah and has a Mission: accompanying their health, accompanying their passive income, accompanying their worship, of the three missions health assistance is going well, while assistance in the field of passive income has not gone as it should. The purpose of this study is to find out the right mentoring strategies in the field of passive income in the elderly in facing and living old age at the Bojonegoro Elderly Assistance foundation. In order to achieve this goal, we conducted research with a qualitative research approach, with interviews of 2 (two) core informants and 6 (six) additional informants who were included in the Forum Group discussion (FGD) about passive income of the elderly, observation of active participation and reading documentation. The results obtained that the right mentoring strategy in the field of passive income through education and training to elderly accompanying nurses and caregivers in investment activities. At least master the calculation of the value of money of the period Future value, so that passive income assistance for the elderly can be applied.   Abstrak: Yayasan Pendampingan lansia memiliki Visi: Mengantarkan para lansia sehat, bermartabat menuju Husnul Khotimah dan memiliki Misi: mendampingi kesehatannya, mendampingi passive income-nya, mendampingi ibadahnya, dari ketiga misinya pendampingan kesehatannya yang berjalan dengan baik, sedang pendampingan di bidang passive income belum berjalan sebagaimana mestinya. Tujuan dari penelitian ini adalah untuk mengetahui strategi pendampingan yang tepat di bidang passive income pada lansia dalam menghadapi dan menjalani masa tua di yayasan Pendampingan Lansia Bojonegoro. Guna tercapainya tujuan tersebut kami mengadakan penelitian dengan pendekatan penelitian kualitatif, dengan wawancara 2 (dua) informan inti dan 6 (enam) informan tambahan yang diikutkan dalam Forum Group discussion (FGD) tentang passive income lansia, pengamatan partisipasi aktif serta membaca dokumentasi. Hasil yang diperoleh bahwa strategi pendampingan yang tepat dalam bidang passive income melalui pendidikan dan pelatihan kepada perawat pendamping lansia dan caregiver dalam kegiatan ber-investasi.  Minimal menguasai perhitungan nilai uang masa yang akan datang (Future value), agar pendampingan passive income lansia dapat diterapkan.